High harmonic generation spectroscopy via orbital angular momentum - Troß, Jan; Trallero-Herrero, Carlos A (My University, 2019)
We present an experimental technique using orbital angular momentum (OAM) in a fundamental laser field to drive high harmonic generation (HHG). The mixing of beams with different OAM allows us to generate two laser foci tightly spaced which generate harmonics that interfere in the far field. Thus, this technique is an OAM based in situ HHG interferometric spectroscopic method. With this tool, we measure the phase and amplitude of the angle dependent multiorbital HHG emission in molecular nitrogen.
Keywords: spectrometry; high harmonic generation; orbital angular momentum